Caracterización fisicoquímica de la cáscara de piña (Ananas comosus) variedad cayena lisa para la obtención de pectina - Coral Guerra, Victor Cristhian (2022)
The objective of this research work was to obtain and characterize pectin from pineapple peel. The work carried out has a quantitative approach with an experimental descriptive deepening level, the study population was constituted by the pineapple shells (ananas comosus) of the Cayena Lisa, of the Belén and model markets, the type of sampling was non-probabilistic random at criteria of the researchers, considering the sample size a maximum of 1500 grams (750 grams, Belén market, 750 grams model market). The pectin extraction process was carried out using citric acid as extraction agents, at pH 3, 4 and 5 in an acid hydrolysis time of 80 minutes at temperatures of 60, 75, 90ºC, applying a 32 factorial design. effect of the independent variables pH and temperature on the response variables Yield. A better extraction yield of 10,11 g/100g was obtained. of pectins with citric acid at pH 3, time of 80 minutes at a temperature of 90ºC. Subsequently, the physicochemical characterization of the pectin was carried out to evaluate its quality, classifying it as low methoxyl pectin. Concluding that it is possible to obtain pectin from pineapple peel (Ananas comosus) Smooth Cayenne Variety.